PENGARUH BAHAN DAN TINGKAT PENGENCER SEMEN MENTOG YANG BERBEDA TERHADAP MOTILITAS PADA SUHU KAMAR - Fitriani Fitriani; Sugiarti Sugiarti (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2019)
This research examined the effect motility quality of Muscovy semen. The quality were used to room temperature levels of semen diluter.   Fress Muscovy semen diluted in 1. Ringer lactate 2. otsu RL dan 3. Sodium chloride and levels 5,10,15X and 0 (control). The result showed that the treatments not significantly affected motility of semen, the highest Muscovy semen in the ringer lactate diluted 5 and 10X (50,00 ± 6,67); (45,55 ± 6,93).The result of the study indicated not significantly affect motility Muscovy semen of determine and diluted.